Neuro-Enhancement Practices across the Lifecourse: Exploring the Roles of Relationality and Individualism - O’Connor, Cliodhna; Nagel, Saskia K. (Frontiers in Sociology, 2017)
One key theme in sociological analysis of neuro-enhancement has been the question of whether the drive for enhancement promotes the cultural value of individualism. It has been argued that neuro-enhancement discourses implicitly propagate new responsibilities that oblige individuals to continually ‘work on’ their brain to ensure its health and productivity. However, much of this critique relies on rather abstract analyses of discursive trends, with relatively little consideration of empirical evidence illuminating the role played by more ‘micro’ social dynamics, such as interpersonal relationships, in the logics and practices of neuro-enhancement. This article proposes a novel perspective on neuro-enhancement by reviewing existing empirical literature enlightening everyday engagements with neuro-enhancement, and suggesting that relationality, rather than pure individualism, may be a better framework for conceptualising these findings. The article advances this argument through a particular focus on two major preoccupations of neuro-enhancement discourses, namely enhancing children’s brains and preventing age-related cognitive deterioration. The article synthesises the empirical evidence showing that these two concerns are essentially relational in experience, and considers how familial relationships and conceptualisations of caregiving lie at the core of how neuro-enhancement concepts and technologies unfold in everyday life. The article offers insights from the philosophical literature on relationality as a conceptual framework to steer further investigation of neuro-enhancement’s impact on contemporary society. A more holistic understanding of the relational dynamics that characterise everyday engagement with neuro-enhancement practices will enable better anticipation of the risks and benefits such practices may entail, due to greater insight into how they are likely to be enacted in context.